DECONSTRUCTION OF TRADITIONAL ART: PRESENTATION STYLE OF CENK BLONK LEATHER PUPPET ON DEWATA TV - Made Darmawan, I Dewa (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2014)
The presentation of Cenk Blonk Leather Puppet on Dewata TV, as a cultural phenomenon with a variety of complex problems, has been observed by most people. However, it is still enthusiastically welcome by the lovers of the Balinese leather puppet both in Bali and outside Bali. It seems that they are not aware of some basic changes in the way it is presented on TV. The way in which it is presented on TV is different from the way in which it is presented on the stage. It is such a cultural art which inspired the writer to explore and analyze in depth the way in which it is presented on TV. This study focuses on how the Cenk Blonk leather puppet is presented on Dewata TV to perform the theme “Dyah Ratna Takeshi”. It was found that the presentation of the Cenk Blonk leather puppet on Dewata TV in its program entitled “Pentas Wayang Kulit’ (the Leather Puppet Performance) was the aesthetic presentation in which the elements of the traditional art were mixed with the modern technology medium (television). The material of the presentation of the Cenk Blonk leather puppet on Dewata TV employed the production of Bali Record which had been reprocessed (deconstructed and reconstructed). Advertisements and other materials were added and some parts were edited so that it suited the pattern of presentation and the slot of time during which it was presented. The Cenk Blonk leather puppet presented on Dewata TV was not completed with any accurate text and context. It gave impression that the traditional art was used to “package” advertisements and other promotions. The presentation of the Cenk Blonk leather puppet on Dewata TV proved to be able to attract many people, especially the young people. They were made to be addicted to the puppetry art. Before, they were not interested in it.